2019
DOI: 10.1038/s41416-019-0422-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections and risk of epithelial ovarian cancer: results from the Nurses’ Health Studies

Abstract: BACKGROUND: Sexually transmitted infections (STIs) are associated with pelvic inflammatory disease and tubal pathologies. Given the tubal origin of a proportion of ovarian cancers, STIs may be relevant in their aetiology. METHODS: Antibodies indicating past infection with Chlamydia trachomatis, Mycoplasma genitalium, herpes simplex virus type 2, and against human papillomavirus oncogenes (L1 and E6+E7 oncoproteins of types 16, 18, 45) were measured in prediagnosis plasma samples in a nested case-control study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 35 publications
6
24
2
2
Order By: Relevance
“…We observed limited heterogeneity in associations by age at blood collection (<60 vs ≥60 years; Table S5). In the analysis considering "high" and "low" positive antibody levels to C. trachomatis cHSP60-1 antibodies and EOC risk, women with high positive antibody levels had higher risk of EOC only among women <60 at blood collection (P het = 0.04; <60 years, Our findings of positive associations between select C. trachomatis antibodies and EOC risk are in line with the results of three previous studies 18,19,25 ; however, others have observed no association. 20,22,24 Previous studies have predominantly analyzed ovarian cancer as a single disease, with small sample size precluding analyses by subtype beyond serous vs nonserous disease.…”
Section: Sensitivity and Subgroup Analysessupporting
confidence: 89%
See 4 more Smart Citations
“…We observed limited heterogeneity in associations by age at blood collection (<60 vs ≥60 years; Table S5). In the analysis considering "high" and "low" positive antibody levels to C. trachomatis cHSP60-1 antibodies and EOC risk, women with high positive antibody levels had higher risk of EOC only among women <60 at blood collection (P het = 0.04; <60 years, Our findings of positive associations between select C. trachomatis antibodies and EOC risk are in line with the results of three previous studies 18,19,25 ; however, others have observed no association. 20,22,24 Previous studies have predominantly analyzed ovarian cancer as a single disease, with small sample size precluding analyses by subtype beyond serous vs nonserous disease.…”
Section: Sensitivity and Subgroup Analysessupporting
confidence: 89%
“…20,22,24 Previous studies have predominantly analyzed ovarian cancer as a single disease, with small sample size precluding analyses by subtype beyond serous vs nonserous disease. [18][19][20]22,24,25 In the current study, we provide a detailed investigation by histotype, observing suggestive heterogeneity by tumor histology. Pgp3 serology indicating current or past infection with C. trachomatis was not associated with EOC risk overall in contrast to two recent studies, 18,25 but was associated with significantly higher risk of mucinous EOC; this has not previously been described.…”
Section: Sensitivity and Subgroup Analysesmentioning
confidence: 78%
See 3 more Smart Citations